2016
DOI: 10.1007/s00056-016-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Can different occlusal positions instantaneously impact spine and body posture?

Abstract: Data for the parameters that varied with different dental occlusions generated high standard deviations. Therefore, within the limitations of this pilot study, we could not conclusively associate dental occlusion to an instantaneous impact on the tested parameters. The posture changes that we detected could also have arisen from individual neuromuscular compensation; a possibility that must now be ruled-in, or out, by further research studies with a higher number of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…The stimulation of the trigeminal nerve by the artificial occlusal disturbance generates a muscular and articular chain reaction, including inclination and rotation of the occiput on the first cervical vertebra, inclination and rotation of the cervical spine, ascent of the ipsilateral scapula, and ascent of the ipsilateral posterior-superior iliac spine 4 , 5 . In the same way, using rasterstereography, März et al recently demonstrated significant alterations in the fleche lombaire in different dental occlusion conditions 35 . The two subjects manifesting unexpected responses to the PSIS test presented atypical physical conditions.…”
Section: Discussionmentioning
confidence: 84%
“…The stimulation of the trigeminal nerve by the artificial occlusal disturbance generates a muscular and articular chain reaction, including inclination and rotation of the occiput on the first cervical vertebra, inclination and rotation of the cervical spine, ascent of the ipsilateral scapula, and ascent of the ipsilateral posterior-superior iliac spine 4 , 5 . In the same way, using rasterstereography, März et al recently demonstrated significant alterations in the fleche lombaire in different dental occlusion conditions 35 . The two subjects manifesting unexpected responses to the PSIS test presented atypical physical conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Non-invasive imaging techniques include the DIERS Formetric examination, which may reveal abnormalities in body posture, gait cycle, balance or loading in early disease. The DIERS system is being increasingly used both for imaging posture and for non-invasive evaluation of treatment outcomes [10, [40][41][42][43]. This study used the DI-ERS Formetric 4D and pedogait systems for verifying postural abnormalities in children with back pain and known discopathy lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study of März et al [ 10 ] the detectable change with the occlusion condition was in the range of half the standard deviation. With a chosen power of 0.8 and 23 variables in the 4 age and 2 sex groups (Bonferroni correction of multicomparison) that were of interest, this resulted in a minimal sample size of 87 per age and gender range.…”
Section: Methodsmentioning
confidence: 99%
“…To understand the link between specific occlusion condition and body posture better, investigations were initiated on immediate effects of different occlusion conditions of the body posture [ 4 , 9 11 , 16 27 ]. In a pilot study, März et al [ 10 ] could demonstrate that the fleche lombaire and the Kyphotic angle changed slightly with a symmetrical occlusal interference with cotton rolls compared to habitual bite position. Due to a high standard deviation, no compelling conclusion could be drawn, and the researcher suggested a similar protocol with a higher number of subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation